Construction and evaluation of a 360 degrees panoramic video on the physical examination of nursing students. (August 2022) - Yang, Tsui-Yun; Huang, Chun-Hsia; An, Chi; Weng, Li-Chueh
Abstract: Aim: The aim of this study was to construct and analyze the content validity and usability for a 360-degree panoramic video for physical examination. Background: Acquiring techniques and ability on physical examination (PE) skill is often difficult. Immersion and simulation provide an opportunity for nursing students in the real situation focus on the PE techniques practice and to improve patient care. The combination of digital instructional materials and innovative teaching strategies is crucial to improving education. Therefore, effective and clear instruction of PE techniques that can enable students confidently to use their skills in clinical practice is an issue that nursing education must address. Methods: This study used a descriptive research design and the technology acceptance model to create a 360-degree video to teach students to perform PE. Content validity and usability were analyzed by five nursing teachers and 53 nursing students who had completed a physical assessment course were invited to assess its usability. Results: The results of the expert review indicated that the content validity of the video scored 0.98 in terms of content relevance, 0.95 in terms of convenience and 0.97 in terms of suitability, suggesting that the video was useful and appropriate for self-practicing. The experts' qualitative feedback indicated that the technical demonstrations in the video were clear and specific and that the video was easy to use. The video increased learning motivation and streamlined learning. The ability to change the video's perspective also increased learning interest. The results of a satisfaction survey were 8.94 points for perceived ease of use, 8.79 points for perceived usefulness, 8.56 points for user attitude toward the video and 9.02 points for continued intention to use the video, indicating that the participants were satisfied with the video. The participants' qualitative feedback indicated that each PE technique was clear and that the ability to change the video's perspective and zooming was useful and novel. Conclusions: The 360-degree panoramic videos were described as a positive learning method for physical examination of nursing students. It provides easy to use and useful to practice PE technique under realistic conditions. Among these outcomes, the 360-degree video can be learned best when teaching PE in nursing education. Accordingly, nursing educators should construct similar videos for the PE of other parts of the body as soon as possible, improve the videos convenience and usefulness and promote their ability to strengthen professional skills.